Natural convection and entropy generation in a three dimensional volumetrically heated and partially divided cavity. Issue 8 (7th November 2016) - Kolsi, Lioua; Abu-Hamdeh, Nidal; Öztop, Hakan F.; Alghamdi, Abdulaziz; Mohamad Naceur, Borjini; Ben Assia, Habib
Abstract : Purpose: The purpose of this paper is to provide a solution for natural convection in a cavity with a partial heater in case of volumetric heating and analysis of the entropy generation. Design/methodology/approach: The control volume method based on three-dimensional (3D) vorticity-potential vector was applied to solve governing equations of natural convection in a 3D cavity with a fin for different governing parameters as external Rayleigh numbers (103= RaE =106), internal Rayleigh numbers 103= RaI =106, partition height (0.25= h =0.75) and partition location (0.25= c =0.75). A code was written by using Fortran platform. Findings: The edge of the fin becomes important on entropy generation. The ratio of the RaI /RaE plays the important role on natural convection and entropy generation. The variation of external Rayleigh number becomes insignificant for the RaI / RaE >1. Originality/value: The originality of this work is to analyze the entropy generation and natural convection in a cubical cavity with volumetrically heating.